Presenteísmo e cultura de segurança no ambiente hospitalar - Zanon, Roosi Eloiza Bolzan (2019)
The Worker Health and Patient Safety interface was observed with a focus on presenteeism and safety culture. Attending to work with signs or symptoms of illness can affect the worker's production and, in the context of health work, can affect patient safety. This study aimed to evaluate the association between presenteeism of health professionals with the safety culture of the patient, in a hospital care setting. This is part of the matrix project "Patient safety culture and injuries to the health of workers in a hospital environment", approved by the Research Ethics Committee under the number 2,447,277 of December 19, 2017. This is an observational epidemiological study, cross sectional, developed in a teaching hospitals, public, tertiary level, 100% SUS, reference in health for the central region of Rio Grande do Sul, Brazil. Data were collected between March and August of 2018, through a questionnaire for sociodemographic characterization, work and health profile; and two self-applicable instruments, validated in Brazil, to measure presenteeism and safety culture: Stanford Presenteeism Scale and Safety Attitudes Questionnaire-Short Form, respectively. Afterwards, they were analyzed by descriptive and analytical statistics. The criteria of Resolution 466/2012, which regulates research with human beings, were respected. 758 professionals participated in the study, most of them female (78.5%), median age 40 years, with companions (75.2%), with children (66.9%), and postgraduate students (58 %). The results were presented in the format of two articles, one of evaluation of presenteeism and another of the association of presenteeism and patient safety climate. Article 1: "Presenteeism of health professionals in a hospital environment". Prevalence of 43.5% of presenteeism; 13.7% had lost productivity; was associated with the following variables: sex, work sector, position, intention to leave work, sleep, physical activity, leisure, medical diagnosis, medication use and leave in the last year. Article 2: "Presenteeism of health professionals: what is its association with the patient safety climate?" Among the presenteeists, the majority evaluated the safety climate negatively, except for the domains Job satisfaction and Stress recognition. The safety climate general had an average of 65.74 (SD = 13.34). We identified associations between presenteeism and safety climate general, and with the domains of Teamwork climate, Safety climate, Stress recognition and Working conditions. Conclusion: High prevalence of presenteeism, which affected the productivity of professionals. The patient safety culture is far from ideal. Health status influenced this evaluation, with the exception of Perceptions of management and Job satisfaction, evaluated respectively as negative and positive, without difference between groups. Concern for colleagues and patients and job satisfaction have been identified as the support points for changes in culture, with a necessary management approach for an ongoing safety culture dialogue.